2019
DOI: 10.4103/jfmpc.jfmpc_703_19
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive tract infections in rural India – A population-based study

Abstract: Context:Reproductive tract infections (RTI) occupy the second position among public health problems.Aims:To find out the prevalence of RTI and its associated conditions among ever married women in the reproductive age group (15–49 years).Settings and Design:This cross-sectional study was conducted among 330 women in a rural area of Poonamallee block at Thiruvallur district in Tamil Nadu from August 2013 to January 2014.Materials and Methods:In this cross-sectional study, the selection of participants was done … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…A similar study also showed that RTI was not associated with age at marriage, pregnancy and contraception use. 4 But in a study conducted in rural Meerut shows that those women who got married before 18 years were significantly associated with RTI. 19 This difference may be due to the fact that age at marriage have been increased over the years.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A similar study also showed that RTI was not associated with age at marriage, pregnancy and contraception use. 4 But in a study conducted in rural Meerut shows that those women who got married before 18 years were significantly associated with RTI. 19 This difference may be due to the fact that age at marriage have been increased over the years.…”
Section: Discussionmentioning
confidence: 96%
“…in various studies conducted in rural areas of Tamil Nadu, Himachal Pradesh and Karnataka, the prevalence of RTI was found to be 21%, 26%, and 32% respectively. 4,11,12 According to NFHS-5 (2019-2020) the prevalence of RTI in India ranges from 4% to 30%. 3 Although the prevalence has come down with various health measures like improved public health care and awareness among women on RTI, it still remains as a public health problem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of vaginal discharge was 11.8% based on a study conducted by Durai V et al [ 13 ]. Based on that, the sample size calculated was 159.…”
Section: Methodsmentioning
confidence: 99%
“…In the healthcare setting, approximately 11% to 38.4% of Indian women seek care for vaginal discharge [9]. A study disclosed that about 21% of Indian women are estimated to have any one type of reproductive tract infection/sexually transmitted infection at any given point in time [10]. Abnormal vaginal discharge (AVD) occurs frequently among women with candidiasis, trichomoniasis, bacterial vaginosis, gonorrhoea, and chlamydia [6].…”
Section: Introductionmentioning
confidence: 99%